Preventive Action to Make Zero Accident for Welding Process - Nila Nurlina; Devina Rosa Hendarti; Rahayu Mekar Bisono (International Journal of Science, Engineering, and Information Technology, 2019)
Each type of work has the risk of being affected by accidents or occupational diseases.  These risks cannot be avoided, but can be minimized.  Welding uses fire and flammable and explosive materials. Given the importance of Occupational, Safety and Health (OSH) in every workplace to increase work productivity, the implementation of OSH is the responsibility of all parties.  Based on observations, many students were absent from lectures due to illness and some were exposed to gram splashes due to welding practices.  Therefore, it is necessary to conduct further research on the application of Occupational health and safety culture as an effort to prevent accidents and diseases caused. The purpose of this research is to make procedure of preventive action on welding process. The research methodology consist of literature study, observation, make danger formulation and make critical assessment. The result of this research show that the highest RPN while the operator do welding.